Simultaneous Analysis of the p16 Gene and Protein in Canine Lymphoma Cells and Their Correlation with pRb Phosphorylation - Leni Maylina; Satoshi Kambayashi; Kenji Baba; Masaru Okuda (Veterinary Sciences, 2022)
Cyclin-dependent kinase inhibitor p16 (CDKN2A) primarily functions as a negative regulator of the retinoblastoma protein (pRb) pathway to prevent pRb phosphorylation, thus playing a critical role in cell cycle arrest. In canine lymphoma cells, methylation due to inactivation of the p16 gene has been reported. However, its protein expression has not been examined in previous studies. In our in vitro study, the gene and protein expression of p16 and phosphorylated pRb were examined simultaneously in eight canine lymphoma and leukemia cell lines (17-71, CLBL-1, GL-1, CLC, CLGL-90, Ema, Nody-1, and UL-1). Methylation of the p16 gene was also explored using the demethylation drug 5-Aza-2′-deoxycytidine (5-Aza). After 5-Aza treatment, p16 gene and protein expression increased and pRb phosphorylation decreased, suggesting that both hypermethylation of the p16 gene and pRb hyperphosphorylation occurred in four out of eight cell lines (CLBL-1, CLC, Nody-1, and UL-1). Moreover, the estimation of p16’s protein expression was better than that of p16’s mRNA expression because the expression of the protein was more stable than those of the gene, and highly related to the phosphorylation of pRb. These results revealed that p16’s protein expression could be a promising biomarker for canine lymphoma cells.